CFD for Underhood Modeling. Development of an Efficient Method - Ljungskog, Emil; Nilsson, Ulf (My University, 2014)
Today's development of cooling systems for passenger cars relies on one-dimensional system simulations, which are heavily dependent on accurate input data obtained from testing or from CFD. Current three-dimensional CFD methods are deemed too computational and workload expensive to be used, which is why the present work was aimed at investigating the possibilities to develop a CFD model of the complete underhood compartment, with a high degree of automation. In the present work, two methods for CFD analysis of underhood flow in passenger cars were developed and compared. Both methods used ANSA for geometry cleanup and STAR-CCM+ as CFD solver, while the volume meshing differed. Method A used a polyhedral mesh created in STAR-CCM+, while a hexahedral mesh was used in method B. Surface wrapping was extensively used in both methods to reduce the manual workload in the geometry cleanup step. In order to validate the methods, they were both applied to a validation case. Both methods underestimated the heat rejection in the radiator with approximately 13% compared to wind tunnel measurements, while the heat rejection in the Charge Air Cooler was underestimated by 4:5% and 6:0% in method A and B, respectively. However, there was a large uncertainty in the experimental results, why further research will be needed to determine the validity of the developed methods. It was concluded that method A showed a larger potential to be used in production cases due to its lower time consumption and superior convergence behavior, even though more work is needed before it can be fully incorporated into the work flow. The time reduction compared to similar methods currently in use at Volvo cars was estimated to roughly 30 %.
Keywords: Strömningsmekanik och akustik; Hållbar utveckling; Energi; Transport; Fluid Mechanics and Acoustics; Sustainable Development; Energy; Transport